2007
DOI: 10.1155/2008/425974
|View full text |Cite
|
Sign up to set email alerts
|

LC‐MS‐MS Method for Determination of Metolazone in Human Plasma

Abstract: A rapid, sensitive and specific method for quantification of metolazone in human plasma using metaxalone as internal standard is described. Sample preparation involved a simple liquid-liquid extraction procedure. The extract was analyzed by high performance liquid chromatography coupled to electrospray tandem mass spectrometry (LC–MS–MS). Chromatography was performed isocratically on a 5 μm C18analytical column (50 mm × 4.6 mmi.d.) with buffer–acetonitrile 20:80 (v/v) as mobile phase. The response to metolazon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…These methods include HPLC for the determination of MET either alone or with furosemide . Also, liquid chromatography‐tandem mass spectrometry (LC‐MS) has been reported for the analysis of MET in human pasma and blood. Regarding LOS, various liquid chromatography methods have been reported for its determination, individually or in combination with other drugs.…”
Section: Introductionmentioning
confidence: 99%
“…These methods include HPLC for the determination of MET either alone or with furosemide . Also, liquid chromatography‐tandem mass spectrometry (LC‐MS) has been reported for the analysis of MET in human pasma and blood. Regarding LOS, various liquid chromatography methods have been reported for its determination, individually or in combination with other drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Literature review reveals that methods have been reported for analysis of Losartan potassium and Metolazone, HPLC method for determination of Losartan potassium in combination with other drugs [ 4 6 ] and few bioanalytical methods are also reported [ 7 – 10 ]. RP-HPLC method for determination of Metolazone [ 11 ] and few bioanalytical methods are also reported [ 12 – 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Metzn is an oral diuretic drug, and is mainly used to cure congestive heart failure and high blood pressure. It is frequently used together with loop diuretics such as furosemide or bumetanide 1 . Metzn indirectly reduces the amount of water reabsorbed in to the bloodstream by the kidney, so that blood volume decreases and urine volume increases.…”
Section: Introductionmentioning
confidence: 99%